Efektivitas Discovery Learning Untuk Meningkatkan Kemampuan Observasi dan Penguasaan Konsep Kesetimbangan Kimia - Reskawati Reskawati; Tasviri Efkar; Emmawaty Sofya (FKIP Universitas Lampung, 2018)
The Effectiveness of Discovery Learning to Improve Observation Skill and Mastery of Concept of Chemical Equilibrium. This study aims to describe the effectiveness of discovery learning model to improving the observation skill and mastery of concept chemical equilibrium. This research was conducted at SMAN 15 Bandar Lampung Teaching Year 2018/2019 using quasi experimental method with Pretest Postest Control Group Design. Sampling of purposive sampling of 3 population classes and samples selected class XI Science 2 as experiment class and XI Science 3 as control class. The effectiveness discovery learning in this study was conducted by using n-gain which was significant between experiment class and control class. The size associated with using the effect size. The result obtained by observation skill and mastery of concept are high, and size of influence is great. With this things, the discovery learning model used has effective and has a large effect measure to improve the observation skill and mastery concept of chemical equilibrium.Keywords: chemical equilibrium, discovery learning, mastery of concept, and observation skill. DOI: http://dx.doi.org/10.23960/jpmipa/v19i2.pp111-122